Performance of isotropic constitutive laws in simulating failure mechanisms in scaled RC beams (Archives of Mechanics - Test, 2020)
Results of numerical calculations of reinforced concrete (RC) beams are presented. Based on experimental results on longitudinally reinforced specimens of different sizes and shapes are investigated. Four different continuum constitutive laws with isotropic softening are used: one defined within continuum damage mechanics, an elasto-plastic with the Rankine criterion in tension and the Drucker–Prager criterion in compression, a formulation coupling elasto-plasticity and damage mechanics and the concrete damaged plasticity (CDP) model implemented in Abaqus. In a softening regime, a non-local theory of integral format is applied to the first three constitutive laws. A fracture energy approach is utilised in CDP model. An ability to reproduce different failure mechanisms observed in experiments for each constitutive model is analysed. A comparison of force-displacement curves and crack patterns between numerical and experimental outcomes is performed.